Epigenetic regulatory pathways involving microRNAs may modulate the host immune response following major trauma. Issue 5 (November 2015) - Owen, Helen C.; Torrance, Hew D.T.; Jones, Timothy F.; Pearse, Rupert M.; Hinds, Charles J.; Brohi, Karim; O'Dwyer, Michael J.
Abstract : BACKGROUND: Posttraumatic nosocomial pneumonia is a common complication resulting in significant morbidity. Trauma-induced immunocompromise is associated with an enhanced susceptibility to pneumonia. In this study, we explore the hypothesis that posttranscriptional epigenetic regulation of gene expression may be an important factor in determining this immune phenotype. We describe the pattern of production of microRNAss (miRs) and their association with nosocomial pneumonia following severe trauma. METHODS: A convenience sample of 30 ventilated polytrauma patients (UKCRN ID: 5637) and 16 healthy controls were recruited. Messenger RNA and protein levels of key cytokines were quantified within 2 hours of the injury and at 24 hours. Three miRs per cytokine were then selected based on miRBase target prediction scores and quantified using polymerase chain reaction. Nosocomial pneumonia was defined using the Centers for Disease Control and Prevention definitions. RESULTS: Median Injury Severity Score (ISS) was 29, and 47% of the patients developed nosocomial pneumonia. miR-125a and miR-202 decreased by 34% and 77%, respectively, immediately following injury, whereas their target, IL-10, increased messenger RNA levels 3-fold and protein levels 180-fold. Tumor necrosis factor α (TNF-α) and IL-12 gene expression decreased by 68% and 43%, respectively, following injury, and this was mirrored by a 10-fold increase in miR-181, an miR predicted to target TNF-α transcripts. Lower levels of miR-125a and miR-374b were associated with the later acquisition of hospital-acquired pneumonia. CONCLUSION: Alteration in the expression of miRs with highly predicted complementarity to IL-10 and TNF-α may be an important mechanism regulating the posttraumatic immunosuppressive phenotype in intensive care unit patients. LEVEL OF EVIDENCE: Retrospective observational study, level III. Abstract : Supplemental digital content is available in the text.